2021
DOI: 10.1002/sdtp.15095
|View full text |Cite
|
Sign up to set email alerts
|

21.3: The Influence of NLOS on Underwater Wireless Optical Communication System Using an InGaN‐based Micro‐LED and NRZ‐OOK Modulation

Abstract: In this paper, we have studied the influence of the total reflection angle on the underwater wireless optical communication (UWOC) link, and built a UWOC link with 7° total reflection angle. Based on this UWOC link, we achieved the maximum data rate of 300 Mbps and a bit error rate (BER) of 3.10×10‐3 under the forward error correction (FEC). In addition, we testified the performance of total reflection UWOC link at different wave frequencies and amplitudes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…However, this can compromise the transmission distance, which requires a cooperative transmission using relay and forward technique that may increase the system complexity due to the power allocation and optimization [88]. As far as experimental trials are concerned, a recent study demonstrated 300 Mbit/s transmission using reflective NLOS with varying surface wave frequencies [89]. However, the study did not consider practical factors such as random surface wave, the effect of divergence angles and scintillation mitigation methods, which leaves room for further research.…”
Section: A Nlos-based Optical Iout System Under Turbulencementioning
confidence: 99%
“…However, this can compromise the transmission distance, which requires a cooperative transmission using relay and forward technique that may increase the system complexity due to the power allocation and optimization [88]. As far as experimental trials are concerned, a recent study demonstrated 300 Mbit/s transmission using reflective NLOS with varying surface wave frequencies [89]. However, the study did not consider practical factors such as random surface wave, the effect of divergence angles and scintillation mitigation methods, which leaves room for further research.…”
Section: A Nlos-based Optical Iout System Under Turbulencementioning
confidence: 99%